THE EXPRESSION ANALYSIS OF TGF-Β1. IGF. AND FGF ON SUPERFICIAL AND DEEP OSTEOCHONDRAL DEFECTS OF KNEE JOINT IN SPRAGUE DAWLEY RATS (PRELIMINARY STUDY) - Basuki Supartono, - (Universitas Sebelas Maret, 2017)
The growth factor is one of the elements that contribute to healing and regeneration of osteochondral defects in knee joint. Stem cell work together with growth factors to produce tissue regeneration. The timing of growth factor expression is very important to determine the timing of observation, during stem cell intervention in osteochondral defect. Here, we showed that TGF-β1, IGF and FGF expressed on chondrocyte cells in osteochondral defect of Sprague Dawley rats temporally. Early expression was observed after 7 days post defect, and disappeared on day 28th . Macroscopic examination exhibit improvement on day 7. The morphogical improvement stayed until day 28th post defect. Taken together, the osteochondral defect induced the expression of TGF-β1, IGF, and FGF temporarily.